Development of an intranasal, universal influenza vaccine in an EU-funded public-private partnership: the FLUniversal consortium - Cnossen, Victor M.; Moreira, Paula C. Leao; Engelhardt, Othmar G.; Samolej, Jerzy; Groeneveld, Geert H.; Jochems, Simon P.; Huisman, Wesley; Pedersen, Gabriel K.; Wørzner, Katharina; Recek, Lukas; Piccini, Giulia; Trombetta, Claudia M.; et al. (Frontiers in Immunology, 2025)
Influenza is a significant global health problem, causing disease and hospitalisations in elderly individuals and infants. While updated vaccines are available every year, their effectiveness is moderate at best. FLUniversal is a European Union funded consortium, aiming to develop a universal influenza vaccine by bringing together partners with expertise in different areas of vaccine development. An intranasal live attenuated vaccine, DeltaFLU, will be produced using an innovative platform; preclinical assessment in animal models and clinical studies using a controlled human infection model (CHIM) will be conducted for assessment of safety, immunogenicity and protective efficacy; and finally, comprehensive immunological analysis of blood and nasal mucosa will elucidate vaccine responses and potential new correlates of protection (CoPs). In addition to a universal influenza vaccine, listed as a top priority by the EU, FLUniversal seeks to deliver an enhanced vaccine manufacturing technology that is superior in terms of efficiency, production costs and production speed - especially critical in the face of a potential new pandemic. Moreover, an influenza CHIM with a focus on harmonisation of clinical procedures and assays will be established to generate translatable and reproducible data. Newly generated knowledge on mechanisms of protection, CoPs and new molecular analysis tools may significantly contribute to our knowledge on influenza infection and influenza vaccines. In conclusion, FLUniversal is an innovative and ambitious public-private partnership, aiming to present a new development pathway for influenza vaccines, and maximising impact by bringing together leading partners from academy and industry with a shared purpose of collaboration and innovation.